Proyecto de inversión para la creación de una empresa de talleres automotriz para la ciudad de Guayaquil - Alvarez Zumba., Gonzalo (2010)
The automobile market in Ecuador exceeded all expectations, reaching in the 2008 a record total sale of 113,000 vehicles. The main brands that are imported for South America are Hyundai, Chevrolet, Toyota, Nissan, Hino, Peugeot, among others. Major automotive companies were motivated to invest in large dealerships in the country mainly in major cities such as Quito, Guayaquil and Cuenca. These companies not only offer new cars, but at the same time it provides the Integrated Automotive Service, but the service is expensive and only focused on its brand vehicles, the purpose is to provide a similar service at lower cost and for all brands on the market. For this reason it is very tentative formation of a new Integrated Services Automotive Workshop Multibrands for light vehicles in the northern sector of the city, as well as born "TALLER SOLUCIONES AUTOMOTRICES AUTOMOTORZ”. AutoMotorz looking to fill a market of 1% of vehicles registered each year traveling a total of 96,707 existing in the city. If this is multiplied a minimum of 2 times per year that a vehicle visits a workshop would have an annual demand of 1,934 vehicles serviced, about 5 cars per day attended. Given the above figures, expectations of reaching that market share, making this project into an attractive business opportunity, focused largely used vehicle market. Finally it became the sensitivity analysis of NPV and IRR, using the simulation tool Crystal Ball, which indicated the various stages of analysis and probability of success, which determined the feasibility and viability of the project.